Pengaruh Motivasi Kerja dan Kepuasan Kerja terhadap Komitmen Organisasional Karyawan pada BPR Nusamba Singaparna Tasikmalaya - Mera Nurlina; Kusuma Agdhi Rahwana; Arga Sutrisna (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
The purpose of the study was to determine, firstly the description of work motivation, job satisfaction, and organizational commitment of employees at BPR Nusamba Singaparna Tasikmalaya, secondly the influence of work motivation and job satisfaction simultaneously on organizational commitment of employees of BPR Nusamba Singaparna Tasikmalaya, thirdly the influence of work motivation partially on commitment. organizational commitment of employees of BPR Nusamba Singaparna Tasikmalaya, and the fourth effect of job satisfaction partially on organizational commitment of employees of BPR Nusamba Singaparna Tasikmalaya. The method used in this study is a quantitative method with a survey approach. The results showed that work motivation was in the very good category, job satisfaction was in the good category, and the organizational commitment of the employees of BPR Nusamba Singaparna Tasikmalaya was in the very good category. There is a simultaneous significant effect of work motivation and job satisfaction on organizational commitment of employees of BPR Nusamba Singaparna Tasikmalaya. There is a partially significant effect of work motivation on organizational commitment of employees of BPR Nusamba Singaparna Tasikmalaya. There is a partially significant effect of job satisfaction on organizational commitment of employees of BPR Nusamba Singaparna Tasikmalaya.